The role of extracellular vesicles in cholangiocarcinoma tumor microenvironment - Zhang, Nuoqi; Shu, Lizhuang; Liu, Zengli; Shi, Anda; Zhao, Liming; Huang, Shaohui; Sheng, Guoli; Yan, Zhangdi; Song, Yan; Huang, Fan; Tang, Yongchang; Zhang, Zongli (Frontiers in Pharmacology, 2024)
Cholangiocarcinoma (CCA) is a highly aggressive malignant tumor that originates from the biliary system. With restricted treatment options at hand, the challenging aspect of early CCA diagnosis leads to a bleak prognosis. Besides the intrinsic characteristics of tumor cells, the generation and progression of CCA are profoundly influenced by the tumor microenvironment, which engages in intricate interactions with cholangiocarcinoma cells. Of notable significance is the role of extracellular vesicles as key carriers in enabling communication between cancer cells and the tumor microenvironment. This review aims to provide a comprehensive overview of current research examining the interplay between extracellular vesicles and the tumor microenvironment in the context of CCA. Specifically, we will emphasize the significant contributions of extracellular vesicles in molding the CCA microenvironment and explore their potential applications in the diagnosis, prognosis assessment, and therapeutic strategies for this aggressive malignancy.